2022
DOI: 10.1007/s10695-022-01094-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impacts of different fasting and refeeding regimes on Nile tilapia (Oreochromis niloticus L.): growth performance, histopathological study, and expression levels of some muscle growth-related genes

Abstract: The current study investigated how different fasting and refeeding regimes would impact Nile tilapia growth performance, histopathological examination, and gene expression of myostatin, myogenin, GH, IGF-1, and NPYa. Nile tilapia fish (n = 120) were randomly allocated into four groups, including the control group fed on a basal diet for 6 weeks (F6), group A starved for 1 week and then refed for 5 weeks (S1F5), group B starved for 2 weeks and then refed for 4 weeks (S2F4), while group C starved for 4 weeks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 104 publications
1
3
0
Order By: Relevance
“…The prolonged fasting period of 45 days resulted in a general decrease in growth performance, such as the reduction in final length from day 30, as well as the reduction in final weight, weight gain, and specific growth rate after 45 days of fasting. These responses corroborate other studies that also used long fasting periods for other fish species [39][40][41][42]. Furthermore, the 14-day refeeding period promoted greater final weight in the fasted/refed group when compared to the basal group, but this period was not enough for this group to reach the weight, length, and weight gain of the fed group.…”
Section: Discussionsupporting
confidence: 88%
“…The prolonged fasting period of 45 days resulted in a general decrease in growth performance, such as the reduction in final length from day 30, as well as the reduction in final weight, weight gain, and specific growth rate after 45 days of fasting. These responses corroborate other studies that also used long fasting periods for other fish species [39][40][41][42]. Furthermore, the 14-day refeeding period promoted greater final weight in the fasted/refed group when compared to the basal group, but this period was not enough for this group to reach the weight, length, and weight gain of the fed group.…”
Section: Discussionsupporting
confidence: 88%
“…For example, complete compensation was reported in some studies, where the starved fish achieved the same weight as the fed fish [ 5 , 12 ]. By contrast, other studies have indicated partial compensatory capacity in Nile tilapia, meaning that feed-restricted fish can increase body weight during refeeding, but cannot reach the weight of continuously fed fish [ 13 , 14 , 15 ]. The physiological processes regulating the compensatory response are not well understood [ 16 ] and can be influenced by the periods of fasting and refeeding, species, age, sex, energy reserves, and environmental factors [ 5 , 7 , 12 ].…”
Section: Introductionmentioning
confidence: 98%
“…Compensatory growth has been widely observed in many teleost species, including Nile tilapia [ 15 , 17 ], Atlantic salmon [ 18 ], rainbow trout [ 9 ], channel catfish [ 19 ], gibel carp [ 20 ], tongue sole [ 21 ], army fish [ 22 ], European minnow [ 23 ], and barramundi [ 24 ]. However, the molecular mechanisms underlying the exaggerated growth phenotype remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, factors such as meal type, fish size, fasting length, water quality, and health status have a great impact on the fish's compensatory growth. Prior studies suggested that Nile tilapia had compensatory growth as a result of intermittent fasting and refeeding [21,22].…”
Section: Introductionmentioning
confidence: 99%